Miss Sloane [videorecording (DVD)] - Chastain, Jessica, 1977-; Strong, Mark, 1963-; Mbatha-Raw, Gugu, 1983- (20th Century Fox Home Entertainment, 2017)
In the world of political power brokers, Sloane takes on the most powerful opponent of her career and will do whatever is required to win.